A new size record of Big eye ilisha, Ilisha megaloptera (Clupeiformes: Pristigasteridae) with a note on its sexual maturity from Hooghly Estuary, India - Ray, Archisman; Bayen, Supriti; Gupta, Subhadeep Das; Das, Basanta Kumar (Journal of the Inland Fisheries Society of India, 2022)
Pristigasteridae family comprising of Genus Ilisha is reported to include 13 species of fish in inshore areas across Indo-Pacific region (Talwar and Jhingran, 1991; Mahmood et al., 2012) with Ilisha filigera being thelargest among all (Whitehead, 1985). All the species exhibit a circum-tropical distribution in estuaries and coastal waters, with eleven in tropical Asia, two in South America and one species in the tropical East Atlantic(Blaber et al., 1998) (Fig. 1). Hooghly estuary is the distributary of Ganga-Bhagirathi river system forming the largest estuary of India (Pantulu, 1966). It is one of the most productive ecosystems and supports important commercial multi-species fisheries. This diverse ecosystem of the Hooghly estuary hosts 76% of the aquatic fauna out of the reported 1498 livingorganisms (Mitra, 2001). The Hooghly estuarine system is mesohaline in nature due to huge freshwater drainage from the tributaries. Ilisha megalopteraÂ (Swainson, 1839), locally known as 'Dhela' in the lower zone of Hooghly estuary, contributes significantly (approximately 2 %) to the total fish landing spectrum. The species is lucrative and admired in the Hooghlyestuarine system owing to its excellent taste and flavour.Â